Platelet-in-Box Colloidal Quantum Wells: CdSe/CdS@CdS Core/Crown@Shell Heteronanoplatelets - Kelestemur, Yusuf (2017)
Here, the CdSe/CdS@CdS core/crown@shell heterostructured nanoplatelets (NPLs) resembling a platelet-in-box structure are developed and successfully synthesized. It is found that the core/crown@shell NPLs exhibit consistently substantially improved photoluminescence quantum yield compared to the core@shell NPLs regardless of their CdSe-core size, CdS-crown size, and CdS-shell thickness. This enhancement in quantum yield is attributed to the passivation of trap sites resulting from the critical peripheral growth with laterally extending CdS-crown layer before the vertical shell growth. This is also verified with the disappearance of the fast nonradiative decay component in the core/crown NPLs from the time-resolved fluorescence spectroscopy. When compared to the core@shell NPLs, the core/crown@shell NPLs exhibit relatively symmetric emission behavior, accompanied with suppressed lifetime broadening at cryogenic temperatures, further suggesting the suppression of trap sites. Moreover, constructing both the CdS-crown and CdS-shell regions, significantly enhanced absorption cross-section is achieved. This, together with the suppressed Auger recombination, enables the achievement of the lowest threshold amplified spontaneous emission (≈20 μJ cm−2) from the core/crown@shell NPLs among all different architectures of NPLs. These findings indicate that carefully heterostructured NPLs will play a critical role in building high-performance colloidal optoelectronic devices, which may even possibly challenge their traditional epitaxially grown thin-film based counterparts.